Influence of using individualised ergonomic handles on upper limb kinematics and neuromuscular activity, perceived comfort and performance during scull rowing - Ertel, G. N.; Pitto, L.; Simon, F. R.; Mornieux, G.; Jehl, J. P.; Gauchard, G. C. (Sports Biomechanics, 2025)
Articular stress, discomfort exposure and the use handles that are not adapted to the task-specific grip during repetitive movements may increase the upper limb injuries risk during boat rowing. Therefore, the purpose of this study was to introduce and evaluate the impact of two individualised ergonomic handles on comfort, upper limb`s biomechanics, and performance in scull rowing, compared to standard handles. These two individualised handle designs were based on the irregular hexagon, and one was further individualised with the rower`s comfort feedback. Perceived comfort, upper limbs kinematics, and neuromuscular activity, as well as boat speed and power production were monitored for 13 elite rowers. The handles tuned on the rower`s comfort feedback increased significantly comfort (9.63 ± 0.3) while maintaining similar performance level (4.22 m.s-1 ± 0.18). The improved comfort (p < 0.001) and the increased wrist extension (p = 0.014) were associated with a better blade orientation feeling. However, the handle orientation setup needs further investigation. Except for Deltoideus Posterior, upper limb neuromuscular parameters, power production and speed were not influenced by the ergonomic handles. New irregular hexagon handle diameters were found for optimal comfort in scull rowing. We recommend individualising irregular hexagon shaped handles for scull rowers wanting to improve comfort.